Analysis of Increasing Case of Acute Respiratory Infections (ARI) in Nickel Mining Environment in Pomalaa District, Kolaka Regency, Southeast Sulawesi - Kudus, Musrifa; Azizi Jayadipraja, Erwin; Syam, Amir; Suriani, Lili (Waluya The International Science of Health Journal, 2022)
Introduction: The mining process that has been carried out for a long time in large quantities often ignores environmental sustainability which in the end can result in various negative impacts that are felt in the short and long term. The purpose of the study was to determine the level of air pollution by Nickel dust and to analyze the relationship between exposure to Nickel dust and ARI disease in people living around the Nickel mining industry in Pomalaa District. Method: This study uses a cross-sectional design using a non-interventional type of research conducted in residential areas around the mining area of ​​PT Aneka Tambang Tbk, Kolaka Regency, Southeast Sulawesi Province as a mining designation area, namely in Pomalaa District. Result: The results showed that the average outdoor air quality for the S02 parameter in the designated area was higher than in the non-designated area, as well as for the N02 parameter, for the H2S parameter in both areas the average value was the same, but for the PM10 value in the designated area is higher than in the non-designated area, while the temperature, humidity, and wind speed in the two areas are almost the same. Conclusion: This is in line with the results of research conducted by Qomariyatus S (in 2007) conducted around the coal mine of PT Aneka Tambang,Southeast Sulawesi showed that the level of respirable dust in the field slightly exceeded the normal threshold value of 2.19 mg/m3.